1990
DOI: 10.1111/myc.1990.33.3.126
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occurrence of Mycotoxins in Some Cereals

Abstract: Thirty samples each of wheat and rice and 22 of maize were screened qualitatively and quantitatively for the presence of mycotoxins out of which 13, 15 and 7 samples respectively were found to be contaminated with different mycotoxins. Aflatoxin was present in 37.4% samples and besides aflatoxin, ochratoxin A, sterigmatocystin, citrinin, rubratoxin and zearalenone were also present in the cereals. The quantity of aflatoxin was highest in rice samples in comparison to wheat and maize. During the preliminary bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Aflatoxins may occur in peanuts, corn (maize) and cottonseed, as well as in many other agricultural commodities (Pittet 2001). Occurrence in rice has also been reported in a number of countries (Reddy et al 2008; Gummert et al 2009): Sri Lanka (Bandara et al 1991), Bangladesh (Dawlatana et al 2002), Japan (Tabata et al 1993), China (Liu and Gao 2006; Wang and Liu 2007), Vietnam (Nguyen et al 2007), Thailand (Shank et al 1972), India (Pande et al 1990; Toteja et al 2006; Reddy et al 2009), the Philippines (Sales and Yoshizawa 2005), Korea (Park et al 2004, 2005a), United Arab Emirates (Osman et al 1999), Turkey (Aydin et al 2010), Tunisia (Ghali et al 2008), Nigeria (Hussaini et al 2007), Côte d'Ivoire (Sangare-Tigori et al 2006b), Uruguay (Piñeiro et al 1996), Brazil (Soares and Rodriguez-Amaya 1989; de Carvalho et al 2010), and the United States (Abbas and Shier 2009), as well as in imported/ marketed rice in the United Kingdom (Scudamore et al 1998; Food Standards Agency (FSA) 2002), Austria (Reiter et al 2010), Iran (Mazaheri 2009) and Sweden (Fredlund et al 2009; Nordkvist et al 2009). The study in Vietnam indicated that the rainy season was a major risk factor for occurrence of AFB 1 in rice (Nguyen et al 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Aflatoxins may occur in peanuts, corn (maize) and cottonseed, as well as in many other agricultural commodities (Pittet 2001). Occurrence in rice has also been reported in a number of countries (Reddy et al 2008; Gummert et al 2009): Sri Lanka (Bandara et al 1991), Bangladesh (Dawlatana et al 2002), Japan (Tabata et al 1993), China (Liu and Gao 2006; Wang and Liu 2007), Vietnam (Nguyen et al 2007), Thailand (Shank et al 1972), India (Pande et al 1990; Toteja et al 2006; Reddy et al 2009), the Philippines (Sales and Yoshizawa 2005), Korea (Park et al 2004, 2005a), United Arab Emirates (Osman et al 1999), Turkey (Aydin et al 2010), Tunisia (Ghali et al 2008), Nigeria (Hussaini et al 2007), Côte d'Ivoire (Sangare-Tigori et al 2006b), Uruguay (Piñeiro et al 1996), Brazil (Soares and Rodriguez-Amaya 1989; de Carvalho et al 2010), and the United States (Abbas and Shier 2009), as well as in imported/ marketed rice in the United Kingdom (Scudamore et al 1998; Food Standards Agency (FSA) 2002), Austria (Reiter et al 2010), Iran (Mazaheri 2009) and Sweden (Fredlund et al 2009; Nordkvist et al 2009). The study in Vietnam indicated that the rainy season was a major risk factor for occurrence of AFB 1 in rice (Nguyen et al 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Developing countries account for 97% of the world's groundnut area and 94% of the total production (FAOSTAT, 2010). However, groundnut yield in this part of the world and particularly in Africa is lower than the world average due to prevailing abiotic, biotic and socioeconomic factors (Pande et al, 2003;Upadhyaya et al, 2006;Caliskan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Groundnut (Arachis hypogaea L.) is an important food and feed crop, which also serve as component of crop rotation in many countries (Pande et al, 2003;Upadhyaya et al, 2006). Groundnuts are also significant source of cash in developing countries that contribute significantly to food security and alleviate poverty (Smart et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Citrinin (CIT), a nephrotoxic mycotoxin mainly produced by Penicillium citrinum, is known to occur as a feed contaminant under natural conditions (Bilgrami et al, 1984;Manickam et al, 1985;Kumari and Nusrath, 1987;Pande et al, 1990;Rajeswari and Char, 1981). It has also been implecated in a fatal human kidney disease, Balkan Endemic Nephropathy, along with ochratoxin A (Stoev, 1998).…”
Section: Introductionmentioning
confidence: 99%